Labour hoarding in Germany: Employment effects of short-time work during the crises - Thomas Kruppe; Theresa Scholz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
During the crisis (2008-09) Germany experienced a huge decrease in GDP. Employment, however, remained surprisingly stable. A whole strand of literature has aimed at quantifying the contribution of short-time work to the German labour market miracle. In the course of this literature we estimate the treatment effect of short-time work on employment at establishment level using a dynamic propensity score matching approach. The analysis is based on data from the IAB Establishment Panel combined with administrative data on short-time work establishments from the Federal Employment Agency. Our results do not indicate any treatment effect of short-time work on employment. – – Während der Wirtschaftskrise (2008-09) erlebte auch Deutschland einen starken Rückgang des Bruttoinlandsprodukts. Die Beschäftigung blieb jedoch erstaunlich stabil. Seitdem zielen viele Publikationen darauf, den Anteil des arbeitsmarktpolitischen Instruments Kurzarbeit am sogenannten deutschen Arbeitsmarktwunder zu quantifizieren. Im Zuge dieser Literatur schätzen wir die kausale Wirkung von Kurzarbeit auf das Beschäftigungsniveau von Betrieben und nutzen dafür den Propensity Score Matching Ansatz. Die Analyse basiert auf Daten des IAB-Beschäftigtenpanels kombiniert mit administrativen Daten der Bundesagentur für Arbeit zur tatsächlichen betrieblichen Inanspruchnahme von Kurzarbeit. Unsere Ergebnisse geben keinerlei Hinweise auf eine kausale Wirkung von Kurzarbeit auf das betriebliche Beschäftigungsniveau.
Keywords: J21; J23; 330; short-time work; crisis; propensity score matching; employment effects